Nursing assistance/care - Gonçalves, Alda Martins (1998)
The present study has the objective of analyzing the development of nursing assistance/care. It emphasizes historical, cultural and social aspects which define this practice. It analyzes assistance/care, dividing it into four stages: non-institutional health care, institutionalized care by religious persons, institutionalized care by lay people and care after nursing became professional. Finally, it analyzes care in today's nursing. This study made it possible to correlate the connotations of care in nursing, that is, the identity crisis of nurses and the theoretical contextualization of care in nursing, according to different authors. We conclude that the dimension of the generic concept of caring and of assistance/caring in nursing changed over time, influenced by different values, convictions and cultures of the authors who write about it.